Reproductive biology in the Antarctic bathydraconid dragonfish Parachaenichthys charcoti - Novillo Estofan, Julio Manuel (2018)
Studies on reproduction of the dragonfishes, Bathydraconidae, are scarce, and within this family, the reproductive biology of Parachaenichthys charcoti was poorly understood. Herein we present a histologic analysis of P. charcoti ovaries together with data on reproductive effort using fish collected with trammel nets in austral summer at Potter Cove, South Shetland Islands (SSI), and compare this information with that reported for the South Georgia congener Parachaenichthys georgianus. In gravid females of P. charcoti, GSI of 16–31%, mature oocytes of 1.8–3.9 mm and total fecundity (TF) of 9025–18,937 oocytes/individual (X ± SD = 12,617 ± 4019, n = 7) were recorded. The histology of the ovaries confirmed the common characteristics of the Notothenioidei observed macroscopically, i.e., two distinct batches of oocytes, one in the previtellogenic stage (primary growing or cortical alveoli stages) and the other in vitellogenesis and likely to be released in the current season. A longer incubation period of P. charcoti compared with P. georgianus is associated to the colder waters at the SSI. Based on our sampling and reproductive effort data, together with the reported nesting behavior for P. charcoti, it is assumed that this species spawns in nearshore, sheltered waters in summer, presumably from late December to February. Spawning periods of both congeners differ from those reported for other notothenioids in the same Seasonal Pack-ice Zone, suggesting divergence in some aspects of the life strategies in the genus Parachaenichthys. Likewise, although there are no substantial differences between P. charcoti and other notothenioids regarding gonadal development, the genus Parachaenichthys shows distinct features in its reproductive strategies (e.g., higher TF) compared with other bathydraconid species.